2012
DOI: 10.1371/journal.pone.0046488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine D2 Receptor Partial Agonist Antipsychotic Aripiprazole on Dopamine Synthesis in Human Brain Measured by PET with L-[β-11C]DOPA

Abstract: Dopamine D2 receptor partial agonist antipsychotic drugs can modulate dopaminergic neurotransmission as functional agonists or functional antagonists. The effects of antipsychotics on presynaptic dopaminergic functions, such as dopamine synthesis capacity, might also be related to their therapeutic efficacy. Positron emission tomography (PET) was used to examine the effects of the partial agonist antipsychotic drug aripiprazole on presynaptic dopamine synthesis in relation to dopamine D2 receptor occupancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Because of the simple and non-invasive procedure after omission of blood sampling, Gjedde-Patlak analysis with reference input function has been widely utilized to investigate the presynaptic function of dopamine neurons, including pathophysiological and clinical studies in patients with various neurologic diseases 1,4,5,9,10,18,20,[40][41][42] and in pharmacological studies. 9,19 We believe that our study provides a further advance for the use of L-[b-…”
Section: Graph Plot Analysismentioning
confidence: 88%
“…Because of the simple and non-invasive procedure after omission of blood sampling, Gjedde-Patlak analysis with reference input function has been widely utilized to investigate the presynaptic function of dopamine neurons, including pathophysiological and clinical studies in patients with various neurologic diseases 1,4,5,9,10,18,20,[40][41][42] and in pharmacological studies. 9,19 We believe that our study provides a further advance for the use of L-[b-…”
Section: Graph Plot Analysismentioning
confidence: 88%
“…Thus, non-human primate studies with 11 C-DOPA PET revealed an inverse relationship between tracer utilization in striatum at baseline, and the decline evoked by challenge with aripiprazole (Ito et al, 2012), suggesting that net agonism at autoreceptors (thus decreasing utilization of exogenous DOPA tracers) was most pronounced in individuals with low basal activation of autoreceptors. Those authors interpreted their findings to support an action of aripiprazole as a stabilizer of dopamine synthesis , with efficacy depending upon individual factors.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves 25%–30% of the maximal dopamine activity in the presence of ARI 14. A recent study showed the effects of ARI in stabilizing dopamine synthesis capacity 15. Its active metabolite, dehydro-aripiprazole, which has similar properties to the parent drug, contributes towards the overall effect 16.…”
Section: Pharmacology Of Aripiprazolementioning
confidence: 99%